2009
DOI: 10.4103/1319-3767.45358
|View full text |Cite
|
Sign up to set email alerts
|

Stapled hemorrhoidopexy: The Aga Khan University Hospital Experience

Abstract: Background/Aim:Stapled hemorrhoidopexy for prolapsing hemorrhoids is conceptually different from excision hemorrhoidectomy. It does not accompany the pain that usually occurs after resection of the sensitive anoderm. This study was carried out to evaluate the clinical outcome of stapled hemorrhoidopexy at The Aga Khan University Hospital.Materials and Methods:A sample of 140 patients with symptomatic second-, third-, and fourth-degree hemorrhoids and circumferential mucosal prolapse underwent stapled hemorrhoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Eric Touzin et al 11 found similar complications in the early post-operative period. Another study by Ali Athar et al 15 showed that early post-operative complications are much less in stapled group. Carlos Walter Sobrado et al, 16 Shalaby et al 18 and Mehigan BJ et al, 19 also showed similar results.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Eric Touzin et al 11 found similar complications in the early post-operative period. Another study by Ali Athar et al 15 showed that early post-operative complications are much less in stapled group. Carlos Walter Sobrado et al, 16 Shalaby et al 18 and Mehigan BJ et al, 19 also showed similar results.…”
Section: Discussionmentioning
confidence: 95%
“…Stapled haemorroidopexy obtains circumferential resection of rectal mucosa in the anal canal, thus preserving the integrity of haemorrhoidal cushions and simultaneously restoring the anal mucosa, the haemorrhoidal cushions and anoderma upwards in the anal canal to their original position thus, restoring normal physiology resulting in less complications. Mean pain scores in several studies like Franc H. Hetzer et al 8 Jean Francois et al 13 , Antonio Lacerda-Filho et al, 14 Ali Athar et al, 15 Carlos Walter Sobrado et al 16 and Sergio Carlos Nahas et al 17 has shown that post-operative pain is less after stapled technique.…”
Section: Discussionmentioning
confidence: 99%